Sum of Expectations of Independent Trials/Proof 2
Theorem
Let $\EE_1, \EE_2, \ldots, \EE_n$ be a sequence of experiments whose outcomes are independent of each other.
Let $X_1, X_2, \ldots, X_n$ be discrete random variables on $\EE_1, \EE_2, \ldots, \EE_n$ respectively.
Let $\expect {X_j}$ denote the expectation of $X_j$ for $j \in \set {1, 2, \ldots, n}$.
Then we have, whenever both sides are defined:
- $\ds \expect {\sum_{j \mathop = 1}^n X_j} = \sum_{j \mathop = 1}^n \expect {X_j}$
That is, the sum of the expectations equals the expectation of the sum.
Proof
The proof proceeds by induction on the number of terms $n$ in the sum.
For all $n \in \Z_{\ge 0}$, let $\map P n$ be the proposition:
- $\ds \expect {\sum_{j \mathop = 1}^n X_j} = \sum_{j \mathop = 1}^n \expect {X_j}$
Basis for the Induction
$\map P 1$ is the case:
- $\ds \expect {\sum_{j \mathop = 1}^1 X_j} = \sum_{j \mathop = 1}^1 \expect {X_j}$
That is:
- $\expect {X_1} = \expect {X_1}$
which is tautologically true.
This is our basis for the induction.
Induction Hypothesis
Now it needs to be shown that if $\map P k$ is true, where $k \ge 1$, then it logically follows that $\map P {k + 1}$ is true.
So this is the induction hypothesis:
$\ds \expect {\sum_{j \mathop = 1}^k X_j} = \sum_{j \mathop = 1}^k \expect {X_j}$
from which it is to be shown that:
$\ds \expect {\sum_{j \mathop = 1}^{k + 1} X_j} = \sum_{j \mathop = 1}^{k + 1} \expect {X_j}$
Induction Step
This is the induction step:
Denote the random variable $Y = \ds \sum_{j \mathop = 1}^k X_j$.
Then we compute:
\(\ds \expect {\sum_{j \mathop = 1}^{k + 1} X_j}\) | \(=\) | \(\ds \expect {Y + X_{k + 1} }\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \expect Y + \expect {X_{k + 1} }\) | Expectation is Linear | |||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{j \mathop = 1}^{k + 1} \expect {X_j}\) | by Induction Hypothesis |
The result follows by the Principle of Mathematical Induction.
$\blacksquare$